Statement of the AGO Kommission Ovar, AGO Study Group, NOGGO, AGO Austria, Swiss AGO, BGOG, CEEGOG, GEICO, and SFOG regarding the use of hyperthermic intraperitoneal chemotherapy (HIPEC) in epithelial ovarian cancer - Harter, Philipp; Bogner, Gerhard; Chiva, Luis; Cibula, David; Concin, Nicole; Fotopoulou, Christina; Gonzalez-Martin, Antonio; Guyon, Frederic; Heinzelmann-Schwarz, Viola; Kridelka, Frederic; Mahner, Sven; Marmé, Frederik; et al. (Bulletin du cancer, 2024)
An international joint statement about the use of hyperthermic intraperitoneal chemotherapy (HIPEC) in ovarian cancer was published in 2016, warning about the uncritical use of HIPEC outside controlled studies. This statement has now been updated after the most recent literature was reviewed by the participating study groups and societies. HIPEC became a treatment option in patients with advanced colon cancer after positive results of a randomized trial comparing surgery and HIPEC versus palliative treatment alone. Although this trial did not compare the added value of HIPEC to surgery alone, HIPEC for the treatment of peritoneal metastases was in the subsequent years generalized to many other cancer types associated with peritoneal carcinomatosis including epithelial ovarian cancer (EOC). In the meantime, new evidence from prospective randomized trials specifically for EOC-patients emerged, with however contradicting results and several quality aspects that made the interpretation of their findings critical. Moreover, three additional trials in colorectal cancer failed to confirm the previously presumed survival benefit through the implementation of HIPEC in peritoneally disseminated colorectal cancers. Based on a still unclear and inconsistent landscape, the authors conclude that HIPEC should remain within the remit of clinical trials for EOC-patients. Available evidence is not yet sufficient to justify its broad endorsement into the routine clinical practice.
Online verfügbar: 24. März 2023, Artikelversion: 4. März 2024
Gesehen am 09.01.2025